Burkina Faso : 2007 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility, Request for Access Augmentation, Requests for Waivers of Nonobservance of Performance Criteria, and Request for Modification of Performance Criteria; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Structural reforms and strong macroeconomic policies of Burkina Faso have promoted economic growth and low inflation over the past decade. Executive Directors welcomed this development, and encouraged the authorities to reduce the fiscal deficit and maintain fiscal and external debt sustainability. They underscored the importance of a sound fiscal policy and a prudent policy framework to improve external competitiveness. They commended tax policy reform and adoption of the new cotton producer price mechanism. In view of this, grant financing is desirable to keep debt sustainable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet